T1 Rev-erbα, a novel anti-inflammatory target, modifies the circadian oscillation of pulmonary inflammation. (16th November 2010) - Blaikley, J; Green, L; Gibbs, J; Farrow, S; Loudon, A; Singh, D; Ray, D
Abstract : Introduction: Most inflammatory diseases demonstrate diurnal variation in severity, for example, chronic obstructive pulmonary disease (COPD) and asthma. We now show that the macrophage inflammatory response is regulated by the circadian cellular clock through Rev-erbα, a nuclear receptor. Additionally, a Rev-erbα ligand (GSK414112) regulates a distinct cytokine network in COPD alveolar macrophages. Results: Circadian oscillation of core clock genes BMAL1, Per2 and Rev-erbα in human macrophages (mdms) demonstrates a functional cellular clock. For the first time we reveal that the inflammatory response is dependent on clock phase, exemplified by altered IL-6 LPS stimulated expression (p<0.01). The critical function of Rev-erbα was confirmed through inhibition of the exaggerated IL-6 response by GSK414112 (p<0.01). Lentiviral knockdown of Rev-erbα expression enhanced the IL-6 LPS response (p<0.05) and attenuated GSK414112's effect. It is known that GSK414112 recruits HDAC3 and NCOR onto Rev-erbα repressing transcription. To define whether Rev-erbα directly interacted with the IL-6 promoter, GSK414112's effect on a series of IL-6 reporter genes was investigated. The full length IL6-luc reporter was repressed by GSK414112 (p<0.01) but mutations to the closely related C/EBP (p<0.01) or 3'AP-1 binding sites (p<0.05) inhibited this effect. ChIP studies confirmed direct interaction of Rev-erbα with the IL-6 promoter. Reporter genes expressing consensus sites for C/EBP and AP-1 showed regulation of these transcription factors by Rev-erbα. Novel Rev-erbα actions were identified through transcriptome profiling of human mdms. SERPINE2, IL-6, PTX3 and MMP-12, all implicated in COPD, are regulated by GSK414112. The analysis also revealed a novel mechanism of action, reverse cholesterol transport, previously implicated in pulmonary inflammation. Luminex analysis on mdms from healthy volunteers and COPD alveolar macrophages revealed that GSK414112 significantly repressed secretion of certain cytokines including IL-6, eotaxin, IL-10, IP-10, G-CSF whilst other cytokines, for example, IL-8, TNFα, MIP 1α were unaffected. Conclusion: Through Rev-erbα an autonomouscellular clock modifies the macrophage LPS response. Ligands for this nuclear receptor exert anti-inflammatory effects through suppression of target gene transcription and up regulation of the cholesterol efflux pathway, employing a novel transcription factor cross-talk mechanism. This mechanism is effective in suppressing glucocorticoid resistant targets as well as targeting the temporal aspects of inflammation.